PP166 From An Institutional Strategic Plan To A Knowledge Transfer Tool For Health Technology Assessment: Case Of Drug-eluting Stents. (2017) - Poder, Thomas; Erraji, Jihane; Coulibaly, Lucien; Koffi, Kouamé; Fisette, Jean-Francois; Dagenais, Pierre; Déry, Véronique
Abstract : INTRODUCTION: Knowledge transfer (KT) of Health Technolgy Assessment (HTA) results presents numerous challenges, one being the lack of time of busy decision makers. Our hospital-based HTA unit is now part of a large network comprising 100 installations. To bridge the gap between complex HTAs and even more limited time by executive officers and managers, we needed to develop a new approach to deliver effectively key HTA messages. We initiated a new strategy with a report on drug-eluting stent (DES). DES may have the potential to eradicate restenosis and the necessity to perform multiple revascularization procedures subsequent to percutaneous coronary intervention (PCI). However, the technology is expensive and some concerns about safety remain. The second generation of DES stents show promising results in terms of efficacy and safety. METHODS: We conducted a systematic review of meta-analyses comparing bare-metal stents (BMS) with second generation DES. Data extracted were used to perform a cost-benefit analysis for our organization. Main findings were illustrated in relation to the strategic plan of our institution. RESULTS: As compared to BMS, the second generation of DES is very effective and potentially leads to huge savings. Safety is improved as regard to myocardial infarction, but not to mortality. For our institution, the use of second-generation DES has the potential to reduce waiting lists for a PCI. In an effort to improve clarity of the results and increase knowledge transfer among managers, we developed a new communication strategy involving the six axes considered as strategic by our Chief Executive Officer, namely: university mission, judicious use of resources, accessibility and quality of care and services, to build for and with the staff, and to act for and with the patient and his family. This led to a smart visual scheme directly showing the results in terms of what is important for our hospital. This initiative was very appreciated by managers. CONCLUSIONS: Using our institutional strategic plan to communicate our results allowed a greater visibility of HTA activities and was greatly appreciated by managers. This will help in disseminating our results locally and in promoting the utility of HTA.